Factors Affecting Stress Levels in Hospitalized Patients after Implementation of Fast.track Protocol in Hepatopancreatobiliary Surgery - Maria Kapritsou; Dimitrios P Korkolis; Margarita Giannakopoulou; Theodoros Katsoulas; Maria Bastaki; Evangelos A Konstantinou (Elsevier, 2020)
Objective: The objective was to explore factors affecting stress levels in hospitalized patients after implementation of fast-track (FT) protocol in hepatopancreatobiliary surgery. Methods: This was a prospective cross-sectional study, where 90 patients were included. Exploration of environmental postoperative stress levels was conducted by serum adrenocorticotropic hormone and cortisol levels, the Intensive Care Unit Environmental Stressor Scale, and three self-reported Numeric Analog Scale questions, with regard to emotional/stress level, specifically "How sad do you feel right now?" "How stressed do you feel right now?" and "How optimistic do you feel right now, about the future?" at 3 time points: (T1) Before surgery, (T2) the day of surgery, and (T3) the 3rd postoperative day. The trial profile is conformed according to the CONSORT guidelines. Statistical analysis was carried out by SPSS software version 22 (IBM SPSS software, Chicago, Illinois, USA) at a significance level of 0.05. Results: Serum cortisol T2levels were positively correlated with the day of removal the drainage tube (rho = 0.235, P = 0.027). Furthermore, serum cortisol T3levels were positively correlated with age and body mass index and negatively with the day of drainage tube removal (rho = 0.231, P = 0.028, rho = 0.235, P = 0.026, and rho = −0.279, P = 0.008, respectively). Conclusions: The findings of this study highlight that after evaluation of stress levels; nurses could interfere and reduce stress levels, knowing the factors which cause the increased stress levels, after the implementation of FT protocols.